Amyotrophic Lateral Sclerosis in a Patient with a Family History of Huntington Disease: Genetic Counseling Challenges. Issue 5 (26th April 2014) - Smith, Andrea L.; Teener, James W.; Callaghan, Brian C.; Harrington, Jack; Uhlmann, Wendy R.
Abstract: Amyotrophic lateral sclerosis (ALS) and Huntington disease (HD) are generally considered to be distinct and easily differentiated neurologic conditions. However, there are case reports of the co‐occurrence of ALS with HD. We present a 57‐year‐old male with a clinical diagnosis of sporadic ALS in the context of a family history of HD. This case adds to the limited literature regarding individuals with a family history of HD who present with features of ALS. There were several genetic counseling challenges in counseling this patient including the diagnostic consideration of two fatal conditions, complex risk information, the personal and familial implications, and the patient's inability to communicate verbally or through writing due to disease progression. DNA banking effectively preserved the right of our patient and his wife not to learn his HD genetic status during a stressful time of disease progression while providing the option for family members to learn this information in the future if desired. We present lessons learned and considerations for other clinical genetics professionals who are presented with similar challenging issues.